2016
DOI: 10.1148/radiol.2016152228
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling to Predict Brain Tumor Grading in Children: Correlations between Histopathologic Vascular Density and Perfusion MR Imaging

Abstract: Purpose To compare arterial spin labeling (ASL) data between low- and high-grade brain tumors in children to establish a cutoff to distinguish low- from high-grade neoplasms and to assess potential correlations between cerebral blood flow (CBF) and quantitative histologic microvascular data. Materials and Methods Approval was obtained from the regional review board. ASL data obtained in 129 children between 2011 and 2015 were retrospectively analyzed. CBF and relative CBF in the most perfused area of each neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
67
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 35 publications
3
67
1
Order By: Relevance
“…Angiogenesis in this group of neoplasms has been investigated and it has been shown that tumors with a higher neovascularity do poorly and have worse outcomes [22] . In our study, we noted wide variations in both hemodynamic and blood brain barrier permeability parameters of high-grade tumors and medulloblastomas, which are consistent with the results of previous imaging studies [5,23] . A wide variety of proangiogenic factors that individually or together play a direct role in medulloblastoma tumor growth, including vascular endothelial growth factor (VEGF), are expressed in embryonal tumors [24] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Angiogenesis in this group of neoplasms has been investigated and it has been shown that tumors with a higher neovascularity do poorly and have worse outcomes [22] . In our study, we noted wide variations in both hemodynamic and blood brain barrier permeability parameters of high-grade tumors and medulloblastomas, which are consistent with the results of previous imaging studies [5,23] . A wide variety of proangiogenic factors that individually or together play a direct role in medulloblastoma tumor growth, including vascular endothelial growth factor (VEGF), are expressed in embryonal tumors [24] .…”
Section: Discussionsupporting
confidence: 92%
“…Few studies have evaluated contrast-enhanced DSC perfusion MRI for grading of pediatric brain tumors, and all of them have found rCBV to be a useful parameter for discriminating high-grade neoplasms from low grade ones [7,17,18] . Arterial spin labeling perfusion techniques have also been used to grade pediatric brain tumors [5] . Vajapeyam et al [8] recently showed the value of DCE perfusion MRI-derived pharmacokinetic parameters for grading of pediatric brain tumors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations